THE SONS OF STAŚ. COLONIAL MASCULINITIES IN FERDYNAND ANTONI OSSENDOWSKI’S YOUTH NOVELS - Forajter, Wacław (Porównania, 2019)
The article The Sons of Staś. Colonial Masculinities in Ferdynand Antoni Ossendowski’s Youth Novels analyses the motif of male initiation in three narrative texts of the Polish popular writer from the interwar period: W poleskiej dżungli [In the Polesian Jungle], Mali zwycięzcy [Little Winners] and Skarb Wysp Andamańskich [The Treasure of the Andaman Islands]. Referring to postcolonial theory and the analysis of ideological discourses of the Second Polish Republic, the author examines novels with the aim to show representations of different cultures, masculinity models that existed in Poland and abroad in that period, and methods of their adaptation for the needs of children’s and youth literature.